Staging of late Larval developmental stages of the microhylid frog, microhyla nepenthicola (anura : microhylidae) - Adi Shabrani, Bin Mohammad Ridzuan (University Malaysia Sarawak, UNIMAS., 2013)
Frog larval form requires separate treatment from its adult form because it has different morphology, diet and breathing mode. Staging table is essential in the study of frog larval development. A newly described species Microhyla nepenthicola Das & Haas 2010 is staged for its larval development.Colour photographs in different aspects are included in documenting the larval development. The late development staging table is recorded starting from Stage 33 until complete metamorphosis.Information of the larval development include time taken for metamorphosis, with changes in limb bud and tail regression are recorded. The metamorphosis duration is fast in this Microhylid frog, which are contributed by its body size. Metamorphosis of Microhyla nepenthicola tadpoles is documented by referring to Gosner (1960), which provided standardised details on each stage of larvae. This will provides a guideline for the larvae stages in Microhyla nepenthicola.